1998
DOI: 10.1007/s003390050789
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of nanostructuring upon nanosecond laser irradiation of a STM tip

Abstract: Abstract. The mechanism of nanostructuring by illumination of scanning probe tips is examined. For that purpose the tip of a scanning tunneling microscope is illuminated with nanosecond and femtosecond laser pulses. The observation of a transient increase of the tunneling current on the timescale of µs is indicative of thermal expansion, which amounts to several nm for the energy density necessary for the purpose of nanostructuring. Furthermore, quantized electrical resistance can be observed upon illumination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…He then estimated that a modelocked excitation would provide sufficient peak power for a good signal-to-noise, while avoiding unwanted photothermal effects (Boneberg et al, 1998;Kawata et al, 1999;Novotny et al, 1997). Additionally, the use of ultrafast laser sources would allow triggering of nonlinear processes.…”
Section: Continuous-wave Versus Ultrafastmentioning
confidence: 98%
“…He then estimated that a modelocked excitation would provide sufficient peak power for a good signal-to-noise, while avoiding unwanted photothermal effects (Boneberg et al, 1998;Kawata et al, 1999;Novotny et al, 1997). Additionally, the use of ultrafast laser sources would allow triggering of nonlinear processes.…”
Section: Continuous-wave Versus Ultrafastmentioning
confidence: 98%
“…Although laser-assisted STM-based nanoprocessing schemes have yielded resolutions on the order of $30 nm [83,84], restrictions on the electrical conductivity of both the material to be processed and the scanning probe tip as well as the ambient working conditions make these methods unsuitable for a wide range of electrically nonconductive and biological materials. Laser nanoprocessing schemes coupled with AFM operated either in contact or noncontact mode provide effective means for overcoming aforementioned drawbacks and enable the development of nanoscopic features of lateral dimensions less than 20 nm.…”
Section: Apertureless Nsom Based Nanomachiningmentioning
confidence: 99%
“…Thus the setup seemed to be promising both for the study of field enhancement effects at sharp tips, a question of great interest in optics, and for surface structuring applications. Further investigations showed that the structuring observed resulted from a thermal expansion of the tip and its subsequent mechanical contact with the surface rather than from field induced effects [4][5][6]. With regard to its application for structuring, the main disadvantage of the illumination of an STM tip is that the process is serial.…”
Section: Introductionmentioning
confidence: 99%